The Effectiveness of Heuristic Vee Model to Improve Students’ Mathematical Problem Solving Skills - Djafar, Kireina; Pomalato, Sarson W.; Takaendengan, Bertu Rianto ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Mathematical problem solving ability is a key component of students’ cognitive development, enabling them to understand, analyze, and apply mathematical concepts in various real-life situations. Despite its importance, many students struggle with problem-solving due to teacher-centered approaches and the lack of interactive, concept-oriented instructional models. This study aims to examine the effectiveness of the Heuristic Vee learning model in improving students’ mathematical problem-solving skills, particularly in the topic of two-dimensional shapes. The research employed a quasi-experimental method using a Non-Equivalent Posttest-Only Control Group Design. The participants were two seventh-grade classes at MTs Negeri 1 Kota Gorontalo, selected through purposive sampling based on class equivalence and teacher recommendations. The experimental group received instruction using the Heuristic Vee model, which involved problem exploration, concept mapping, and guided reflection, while the control group was taught through the direct instruction method. Data were collected through a post-test consisting of essay questions based on Polya’s four problem-solving stages. All instruments were validated by experts and tested for reliability. Data analysis included descriptive statistics, normality and homogeneity tests, independent t-tests, and effect size measurement. The results showed that the experimental group achieved a higher mean post-test score (49.83) than the control group (31.70), with a significant t-value of 3.458 > 2.002 at the 5% significance level. The effect size (Cohen’s d = 0.89) was categorized as high. These findings indicate that the Heuristic Vee model significantly enhances students’ mathematical problem-solving skills and serves as an effective strategy for promoting student-centered and meaningful mathematics learning.